2018
DOI: 10.1080/13557858.2018.1520815
|View full text |Cite
|
Sign up to set email alerts
|

Pathways from racial discrimination to cortisol/DHEA imbalance: protective role of religious involvement

Abstract: Our findings support the socio-psychobiological model of racism and health [Chae et al. 2011 . "Conceptualizing Racial Disparities in Health: Advancement of a Socio-Psychobiological Approach." Du Bois Review: Social Science Research on Race 8 (1): 63-77. doi: 10.1017/S1742058X11000166 ] and suggest that the psychological toll of RD can confer physiological consequences. Moreover, ORI may disrupt pathways from RD to cortisol/DHEA ratio by buffering the psychological toll of RD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 59 publications
0
15
0
Order By: Relevance
“…One study reported that Black American adults who participated in an experimental study after national coverage of a racial macrostressor exhibited dysregulated cortisol outcomes compared to those who participated before the incident received national coverage, and this effect was especially pronounced among Black American women (Richman & Jonassaint, 2008). Prior research using surveys indicated that racial discrimination experiences were not associated with overall levels of cortisol (Lee, Eisman, et al, 2018; Lee, Peckins, Heinze, et al, 2018) the cortisol/dehydroepiandrosterone ratio (Lee, Peckins, Miller, et al, 2018), or overnight cortisol levels (Brody et al, 2014). One study indicated that racial discrimination experiences were linked to higher waking levels and a steeper diurnal slope among Black American adults (Fuller-Rowell, Doan, & Eccles, 2012), whereas another study reported that racial discrimination experiences were related to lower waking cortisol levels, lower average cortisol output, and flatter diurnal slopes among Black American adults (Adam et al, 2015).…”
Section: Racial Discrimination and The Hpa Axismentioning
confidence: 99%
“…One study reported that Black American adults who participated in an experimental study after national coverage of a racial macrostressor exhibited dysregulated cortisol outcomes compared to those who participated before the incident received national coverage, and this effect was especially pronounced among Black American women (Richman & Jonassaint, 2008). Prior research using surveys indicated that racial discrimination experiences were not associated with overall levels of cortisol (Lee, Eisman, et al, 2018; Lee, Peckins, Heinze, et al, 2018) the cortisol/dehydroepiandrosterone ratio (Lee, Peckins, Miller, et al, 2018), or overnight cortisol levels (Brody et al, 2014). One study indicated that racial discrimination experiences were linked to higher waking levels and a steeper diurnal slope among Black American adults (Fuller-Rowell, Doan, & Eccles, 2012), whereas another study reported that racial discrimination experiences were related to lower waking cortisol levels, lower average cortisol output, and flatter diurnal slopes among Black American adults (Adam et al, 2015).…”
Section: Racial Discrimination and The Hpa Axismentioning
confidence: 99%
“…In one study, the indirect effect of racial discrimination on African American emerging adults' depressive symptoms was buffered by organizational religious involvement (D. B. Lee, Peckins, et al, 2018). A similar effect was found in a study by Parenteau and colleagues on the role of religious orientation as a buffer against racial discrimination on undergraduate problematic drinking.…”
Section: Organizational Religious Involvement Racism and Problematic ...mentioning
confidence: 58%
“…Greater racial discrimination has also been linked to increased catecholamine activity among Black men and women [ 80 , 81 ]. Importantly, some evidence suggests that protective factors such as higher educational attainment, higher income, and greater religious engagement can buffer the association between discrimination and neuroendocrine activity among Black Americans [ 82 , 83 ].…”
Section: Discussionmentioning
confidence: 99%